Association of Risk Factors with Coronary Angiographic Findings of Female Patients with Acute Myocardial Infarction at a Tertiary Hospital of Bangladesh - Safa, Jinnat Fatema Saira; Murshed, AKM Manzur; Das, Prabir Kumar; Dey, Ashish; Bhattacharjee, Biplob; Awal, Anisul (Bangladesh Heart Journal, 2019)
Background: Coronary artery disease (CAD) is the leading cause of mortality and morbidity of women in developed and developing country. Although women in low and middle income countries have worse situation they are least studied. Cardiovascular risk factors assessment and their correlation with angiographic severity in female patients is essential to take preventive strategy and timely intervention. Aim: The aim of this study was to evaluate the major risk factors of coronary artery disease and to study the relation of those cardiovascular risk factors with coronary angiographic findings in female patients with AMI . Methods: This was a cross-sectional observational study carried out in the department of Cardiology, Chittagong Medical College Hospital (CMCH) from January 2017 to December 2017. One hundred and fifty consecutive female patients diagnosed as acute myocardial infarction (AMI) who subsequently underwent coronary angiography (CAG) during the study period were included in the study. Data regarding demographic, clinical & laboratory features were recorded. Severity of CAG findings was assessed by Gensini score. Results: The mean age of the study population was 53.19(±10.71) years. Hypertension was the commonest cardiovascular risk factor (78%) in this study followed by obesity (68%), dyslipidaemia (62%) and diabetes mellitus (57.3%). About 80% patients had clustering of ≥3 risk factors. Proportion of patients having STsegment elevation myocardial infarction (STEMI) and non ST-segment elevation myocardial infarction (NSTEMI) were 47% and 53% respectively. Thrombolytic was the most frequently used treatment modality for the management of STEMI patients. Double Vessel Disease, type B lesion with Gensini score ≥20 were the most common CAG findings. Triple vessel disease and severe CAD (Gensini score ≥20) were more in women with three or more risk factors. A significant (p<0.05) linear correlation was found between Gensini score and age, triglyceride level and total cholesterol level. Other factors, including, obesity, family history, hypertension, diabetes mellitus, menopausal status were found to be more prevalent among severe coronary artery disease on CAG but the differences were not statistically significant (p>0.05). Conclusion: The present study showed a significant relation of having multiple cardiovascular risk factors with developing more aggressive angiographic findings. It also revealed that Bangladeshi female patients of AMI had clusters of cardiovascular risk factors and presence of multiple risk factors is a predictor of severe coronary artery disease. Bangladesh Heart Journal 2019; 34(2) : 100-110